(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Gulshan-Baridhara lake located in and around Gulshan, Banani and Baridhara, has always been Dhakas most exclusive residential area mainly because of the pristine lake. The lake is elongated in a north south direction and surrounded mainly by residential areas and some industrial units as well. To evaluate the pollution level of the sediment of the lake, samples were collected from 4 selected locations in 4 different seasons. Four different media were used to study the aerobic heterotrophic, enteric and related bacterial count. Aerobic heterotrophic bacterial count was in the range of 1.1 × 104 to 1.2 ×106 cfu/g in sediment sample, while enteric and related bacterial count in 3 different media (SS agar, MacConkey agar and Cetrimide agar) were 1×100 to 1.5×104 cfu/g, 1×100 to 6×104, and 1×100 to 1.1×103 cfu/g in sediment, respectively. Out of 23 bacterial isolates 18 were Gram-positive and 5 were Gram-negative. Among the Gram-positive, all were rod shaped spore former and under the genus Bacillus. Out of 5 Gram-negative isolates 2 were the member of Pseudomonas, remaining 3 strains were Escherichia, Aeromonas and Enterobacter. Total nitrogen and phosphorus level along with the presence of different bacterial strains clearly indicated that Gulshan lake sediment was polluted with the chemical and bacterial pollutants. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15596 J. Asiat. Soc. Bangladesh, Sci. 38(2): 155-161, December 2012